RADIOGENIC HELIUM ISOTOPE FRACTIONATION: THE ROLE OF TRITIUM AS 3HE PRECURSOR IN GEOCHEMICAL APPLICATIONS - Tolstikhin I.N.; Kamensky I.L.; Nivin V.A.; Gannibal M.A.; Lehmann B.E.; Loosli H.H.; Orlov S.P.; Ploschansky L.M.; Tokarev I.V. (My University, 1999)
Reduced 4He/3He ratios, e.g., down to ≈1/100 times those expected from radiogenic production, were observed in sedimentary rocks. Formation and history of these rocks eliminate a contribution of mantle 3He-bearing fluid. To explain the difference between the observed and the calculated production 4He/3He ratios Loosli et al. (1995) and Tolstikhin et al. (1996) suggested a different behaviour of helium and tritium in damage tracks produced by emission of these nuclides. Generally, the tracks cross grain boundaries or some imperfections within a rock or mineral allowing a fast loss of noble 4He and 3He atoms. However, radiogenic 3He has the precursor 3H, generated in the exothermic 6Li(nt, α)3H + 4.5 MeV reaction. The energetic tritons produce damage tracks comparable with those from α-decay of U and Th series. If 3H is chemically bound within a track, and the track is able to recover via some diagenetic process before the 3H decay, then 3H and daughter 3He atoms are trapped within the recovered track. This mechanism would explain the shorter residence time of 4He in the rocks/minerals than of 3He; therefore, 4He/3He ratios could decrease through time.